Uji Konduktivitas Benih pada Beberapa Genotipe Mutan Kedelai Hitam Generasi Mutan ke Tiga (M3) - Siti Novridha Andini; Miranda Ferwita Sari; Septiana Septiana; Onny Chrisna Pandu Pradana (Politeknik Negeri Lampung, 2021)
At the selection stage in breeding with gamma irradiation mutation induction, seeds from the previous generation are needed to be planted in the field to obtain the next generation of mutants. The seeds before planting have undergone a storage period, during the storage period if the temperature, humidity, and storage conditions are not right it will affect the viability and vigor of the seeds which can reduce the germination of seeds in the field Tests to determine seed vigor can be done by conducting a conductivity test (DHL). The purpose of this study was to determine the conductivity value of each genotype of the third generation mutant and the percentage of germination of black soybean seeds during the storage period. This study used a non-factorial completely randomized design (CRD) with 10 mutant genotypes and 1 control (without irradiation), and each treatment was replicated four times. Observation variables were electrical conductivity/conductivity, germination rate, growth speed, growth synchronously, vigor index, and maximum growth potential. Based on the conductivity/DHL test, genotypes with high Conductivity/DHL values ​​have a low percentage of germination, but the percentage of germination is still above 80% during the storage period, so it is expected that they will still have high germination ability in the field. Keywords: electrical conductivity, black soybean, and conductivity.